2022
DOI: 10.1038/s41598-022-18681-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimized production and fluorescent labeling of SARS-CoV-2 virus-like particles

Abstract: SARS-CoV-2 is an RNA enveloped virus responsible for the COVID-19 pandemic that conducted in 6 million deaths worldwide so far. SARS-CoV-2 particles are mainly composed of the 4 main structural proteins M, N, E and S to form 100 nm diameter viral particles. Based on productive assays, we propose an optimal transfected plasmid ratio mimicking the viral RNA ratio in infected cells. This allows SARS-CoV-2 Virus-Like Particle (VLPs) formation composed of the viral structural proteins M, N, E and mature S. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…In SARS-CoV-2 studies, the real virus or infectious materials must be manipulated in biosafety level 3 laboratories, limiting the investigation rate of the SARS-CoV-2 life cycle. The application of substitutes such as pseudovirus, viral protein-expressing cells and VLPs have been developed for SARS-CoV-2 studying [25]. The pseudovirus of SARS-CoV-2 was a kind of chimeric virus with SARS-CoV-2 spike and other structure proteins derived from different viruses, such as lentivirus or Vesicular stomatitis virus (VSV) [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In SARS-CoV-2 studies, the real virus or infectious materials must be manipulated in biosafety level 3 laboratories, limiting the investigation rate of the SARS-CoV-2 life cycle. The application of substitutes such as pseudovirus, viral protein-expressing cells and VLPs have been developed for SARS-CoV-2 studying [25]. The pseudovirus of SARS-CoV-2 was a kind of chimeric virus with SARS-CoV-2 spike and other structure proteins derived from different viruses, such as lentivirus or Vesicular stomatitis virus (VSV) [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The labeling of SARS-CoV-2 VLPs with fluorescence could be very useful to visualize either viral entry or assembly in target cells. The fusion of structural proteins of SARS-CoV-2 (including S, M and N proteins) with a fluorescence protein such as green fluorescence protein (GFP) had been used to visualize SARS-CoV-2 VLPs in cells [13,25]. Given that the molecular weight of fluorescent proteins is around 25-30 kDa, it is possible that tagging with fluorescence proteins may hinder the biological functions of SARS-CoV-2 structure proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that co-transfection of plasmids expressing each of the four SARS-CoV-2 structural proteins allows for secretion of virus-like particles (VLPs) [19,61,62], which is concordant with earlier studies with other CoV structural proteins [63,64]. However, we observed that when Spike, E, M and N expression vectors were co-transfected into cells, 6-TG treatment not only altered the accumulation and processing of Spike, but also dramatically reduced accumulation of E and M proteins (Fig 5A).…”
Section: -Thioguanine Causes a Coronavirus Assembly Defectmentioning
confidence: 99%
“…More recently, TIRF-M was indeed combined with super-critical angle fluorescence detection for high axial resolution and sharp localization pointing precision [5]. In the field of virology, these techniques have proven their strength and use [6][7][8][9][10][11]. For the lack of sensitivity, as the fluorescence emission is, among others, proportional to the intensity of the excitation field, we proposed to act on the local evanescent exciting field by introducing resonant dielectric multilayer (DM) coated coverslips while limiting its impact over the fluorescence collection efficiency.…”
Section: Introductionmentioning
confidence: 99%